Model Predictive Control of a Fault-Tolerant- Hybrid Excitation Axial Field-Flux-Switching Permanent Magnet Motor - Saadat Jamali Arand; Javad Rahmani Fard (AUT Journal of Electrical Engineering)
To improve the performance of the fault-tolerant-hybrid excitation axial field flux-switching (FT-HEAFFS) motor and attain the minimum copper loss, a fault-tolerant control method based on the model predictive control algorithm is proposed. Considering a 6 stator slots/13- rotor poles FT-HEAFFS machine as the control object, under the open circuit failure of single-phase winding, the minimum cropper loss fault-tolerant method based on the model predictive torque control (MPTC) and direct torque control are studied and analyzed, respectively. The feasibility and effectiveness of the proposed fault-tolerant control method are verified. The research results showed that both methods could make the speed, torque and stator flux-linkage almost unchanged, ensuring the stable operation of the system. Compared with direct torque control, the model predictive flux control had smaller flux-linkage ripple before and after the open circuit failure.